High-conductivity aluminum strip and preparation method and application thereof
By adjusting the composition ratio of rare earth elements and graphene and employing a stepwise melting process, combined with control over the rolling process, a rare earth-enriched passivation layer and oriented graphene arrangement are formed, solving the problems of improving the conductivity and stability of pure aluminum and achieving the preparation of high-conductivity aluminum strips.
Patent Information
- Application Number
- CN202611494253.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-11-03
AI Technical Summary
Existing technologies are insufficient to effectively improve the conductivity of pure aluminum. Graphene has poor dispersion in aluminum melt and is prone to forming harmful phases, resulting in limited improvement in conductivity. Furthermore, existing solutions fail to incorporate microstructure control into the rolling process, affecting batch stability.
By limiting the composition ratio of rare earth elements and graphene, and combining the microstructure control of the step-by-step melting and rolling processes, a rare earth-enriched passivation layer is formed, and the graphene is oriented along the rolling direction to prepare a high-conductivity aluminum strip.
Significantly improves the conductivity of aluminum strip, ensures material processing and forming performance, achieves stable improvement in conductivity, and meets the needs of high-power electronics and new energy battery fields.
Smart Images

Figure CN123027482A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of aluminum alloy processing technology, specifically to a high conductivity aluminum strip, its preparation method, and its application. Background Technology
[0002] Industrial pure aluminum strip is lightweight, corrosion-resistant, and has good processability, making it widely used in electronic heat dissipation, conductive connections, and new energy battery components. 1070 pure aluminum has high purity and is a commonly used base material for high-conductivity aluminum components, exhibiting stable conductivity under normal annealing conditions. With the increasing integration of high-power electronic devices and the growing current density of power batteries, the industry has placed higher demands on the electrical and thermal conductivity of aluminum substrates. Reducing heat generation and component weight while maintaining the same current carrying capacity has become an important development direction for conductive aluminum materials.
[0003] Current methods for improving the conductivity of pure aluminum primarily focus on matrix purification, such as borylation and the addition of single rare earth elements. However, these methods offer limited improvements in conductivity and are insufficient to meet higher application demands. Some studies have attempted to add graphene to aluminum to construct conductive pathways, but graphene exhibits poor wettability in molten aluminum, is prone to agglomeration, and readily reacts with aluminum at high temperatures to form harmful brittle phases. This not only fails to deliver the expected conductivity gains but also negatively impacts subsequent rolling processing performance. Directly blending rare earth elements with graphene fails to create an effective synergy, resulting in a conductivity effect that is essentially a simple superposition of the two methods, failing to overcome the current conductivity bottleneck of pure aluminum. Furthermore, most existing solutions focus solely on compositional adjustments without considering microstructure control during the rolling process, leading to room for improvement in batch-to-batch performance stability during mass production. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a high-conductivity aluminum strip, its preparation method, and its application. By limiting the composition ratio of rare earth elements and graphene, combined with a step-by-step melting process, and by controlling the microstructure during rolling, the invention solves the problems of poor dispersion of graphene in aluminum melt, easy formation of harmful phases at the interface, and limited improvement in conductivity. While ensuring the material's processing and forming performance, the invention steadily improves the conductivity of the aluminum strip. The entire process is compatible with existing conventional aluminum strip production lines and meets the needs of high-power electronics, new energy batteries, and other fields for high-conductivity aluminum materials.
[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: On one hand, a high-conductivity aluminum strip, the aluminum strip using 1070 pure aluminum as a matrix, containing graphene, cerium, and lanthanum; by mass percentage, graphene is 0.005%–0.5%, cerium is 0.02%–0.3%, and lanthanum is 0.02%–0.3%; the total mass ratio of cerium and lanthanum to the mass ratio of graphene is 2:1–10:1; the conductivity of the aluminum strip is not less than 62% IACS.
[0006] Furthermore, the mass ratio of cerium to lanthanum is 1:1 to 1:2, which can take into account both the purification effect of matrix impurities and the passivation effect of graphene interface, so that the two form a stable synergistic effect.
[0007] Furthermore, the graphene is few-layer graphene with a sheet diameter of 0.5–10 μm, 1–5 layers, a carbon purity of not less than 99.5%, and an oxygen content of not more than 0.3%, thereby reducing the scattering effect of graphene's own defects on electron transport and ensuring that its intrinsic conductivity is fully utilized.
[0008] Furthermore, in the 1070 pure aluminum, the iron content is no higher than 0.12%, the silicon content is no higher than 0.08%, and the total impurity content is no higher than 0.3%, thereby controlling the level of basic impurities and reducing the lattice scattering loss caused by solid solution impurities.
[0009] Furthermore, a rare earth enriched passivation layer is formed at the interface between the graphene and the aluminum substrate. The thickness of the rare earth enriched passivation layer is 2-5 nm, and it contains cerium carbide, lanthanum carbide and aluminum rare earth intermetallic compounds to suppress the formation of brittle aluminum carbide phase at the interface, while ensuring the electron transport efficiency at the interface.
[0010] Furthermore, the aluminum substrate is formed <111> The rolled texture, with graphene oriented along the rolling direction, further reduces grain boundary scattering during electron transport and improves conductivity along the rolling direction.
[0011] On the other hand, a method for preparing a high conductivity aluminum strip includes the following steps: S1 matrix smelting and rare earth purification: 1070 aluminum ingots are heated to 720-740℃ and completely melted. Aluminum-cerium master alloy and aluminum-lanthanum master alloy are added, stirred evenly, and then refined with inert gas. After standing, the surface slag is removed. S2 Low-Temperature Dispersed Graphene: The melt treated by S1 is cooled to 680-710℃, and pre-coated graphene composite powder is added. Electromagnetic stirring combined with ultrasonic field-assisted dispersion is used to obtain the melt to be cast after dispersion. S3 casting billet: The molten material to be cast is made into a billet by casting or continuous casting and rolling; S4 Rolling and Annealing: The billet is hot-rolled and cold-rolled to the target thickness in sequence, and then annealed at low temperature to obtain the finished aluminum strip.
[0012] Furthermore, in step S2, the graphene composite powder is a core-shell structured powder with a surface coated with nano-aluminum powder; the frequency of the ultrasonic field is 20–40 kHz, and the power density is 0.5–1.5 W / cm². 3 The dispersion time is 5-15 min, which improves the wettability of graphene and aluminum melt, enhances the dispersion uniformity through the action of composite force field, and reduces graphene agglomeration.
[0013] Furthermore, in step S4, the hot rolling opening temperature is 450–500℃, and the total hot rolling reduction rate is not less than 75%; the total cold rolling reduction rate is not less than 60%, and the single-pass reduction rate is 15%–25%; the low-temperature annealing temperature is 280–320℃, and the holding time is 1–2 hours. The preferred texture is induced by rolling with a large reduction rate, and the microstructure is stabilized by low-temperature annealing, thereby achieving a balance between electrical conductivity and mechanical properties.
[0014] On the other hand, the aforementioned high conductivity aluminum strip can be used in heat dissipation devices, soft connections for new energy vehicle batteries, or copper-aluminum composite conductive strips.
[0015] Compared with existing technologies, this high conductivity aluminum strip, its preparation method, and its application scheme have the following advantages: I. This invention, by defining the ratio of rare earth elements to graphene and employing a stepwise melting method of first purifying the matrix with rare earth elements and then dispersing graphene, enables rare earth elements to form an enriched passivation layer in situ at the interface between graphene and the aluminum matrix. This improves the dispersion effect of graphene and inhibits the formation of harmful phases at the interface, achieving a synergistic effect between the rare earth purification matrix and the construction of conductive pathways by graphene. As a result, the conductivity of the aluminum strip is significantly higher than the combined effect of the two methods alone, breaking through the conductivity bottleneck of traditional pure aluminum.
[0016] Second, this invention induces the formation of a specific rolling texture in the aluminum matrix through a combination of hot rolling, cold rolling and low-temperature annealing. At the same time, it causes the graphene to align in the direction of rolling, further reducing the scattering loss during electron transmission. While ensuring the material's processing and forming performance, it steadily improves the conductivity. The entire process can be adapted to existing conventional aluminum strip production lines and has good performance stability during mass production.
[0017] Other advantages, objectives and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination or study, or may be learned from the practice of the invention. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 This is a schematic diagram of the manufacturing process of the high conductivity aluminum strip of the present invention; Figure 2This is a flow chart of the key processes for low-temperature graphene dispersion in this invention. Figure 3 This is a flow chart of the key processes for rolling and annealing microstructure control in this invention. Detailed Implementation
[0020] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below.
[0021] In the following examples and comparative examples, conductivity was measured using an eddy current conductivity meter at room temperature. Before testing, the sample surface was polished to remove the oxide layer. Tensile strength and elongation were measured using a universal testing machine according to the tensile testing methods for metallic materials. Interface microstructure was observed using a high-resolution transmission electron microscope. Texture orientation was detected using X-ray diffraction.
[0022] Example 1 The high conductivity aluminum strip in this embodiment uses 1070 pure aluminum as the matrix. By mass percentage, the addition of graphene is 0.05%, cerium is 0.15%, and lanthanum is 0.15%. The mass ratio of cerium to lanthanum to graphene is 6:1, and the mass ratio of cerium to lanthanum is 1:1. The 1070 pure aluminum contains 0.10% iron, 0.06% silicon, and 0.25% total impurities. The graphene used is few-layer graphene with a sheet diameter of 2 to 5 μm, 2 to 4 layers, a carbon purity of 99.6%, and an oxygen content of 0.25%. The graphene composite powder is coated with nano-aluminum powder on the surface of the few-layer graphene using vapor deposition. The average particle size of the aluminum powder is one-eighth the diameter of the graphene sheet, forming a core-shell structure. This coating improves the wettability of graphene and molten aluminum and reduces the tendency for agglomeration.
[0023] The preparation process is as follows Figure 1 The process flow shown is as follows, with specific steps as follows: S1 Matrix Melting and Rare Earth Purification: 1070 aluminum ingots are placed in a resistance melting furnace and heated to 730℃ until completely melted. Aluminum-cerium master alloy and aluminum-lanthanum master alloy are added, with the aluminum-cerium master alloy containing 10% cerium by mass and the aluminum-lanthanum master alloy containing 10% lanthanum by mass. Mechanical stirring is performed for 5 minutes until the master alloys are completely dissolved. Then, argon gas is introduced for rotary jet refining for 8 minutes. After refining, the mixture is allowed to stand for 10 minutes, and the slag on the surface of the melt is removed.
[0024] S2 Low-Temperature Dispersion of Graphene: This step is performed as follows Figure 2The process shown involves cooling the S1-treated melt to 690°C and then uniformly adding the prepared graphene composite powder through a closed feeding device. Electromagnetic stirring is activated, and an ultrasonic field is simultaneously applied to the melt at a frequency of 30 kHz and a power density of 1.0 W / cm³. 3 Disperse the mixture for 10 minutes to obtain the melt to be cast.
[0025] S3 casting billet: The molten material to be cast is poured into a flat billet with a thickness of 20mm, and the temperature is controlled at 680℃ during the casting process.
[0026] S4 rolling and annealing: This step is performed as follows Figure 3 The process shown involves heating the billet to 480℃ and holding it for 30 minutes before hot rolling. The hot rolling process consists of three passes with a total reduction of 80%, resulting in a billet thickness of 4mm. This is followed by cold rolling, which takes six passes with a single-pass reduction controlled between 18% and 22%, resulting in a total reduction of 75%. The cold-rolled aluminum strip has a thickness of 1mm. The cold-rolled aluminum strip is then placed in an annealing furnace and annealed at 300℃ under argon protection for 1.5 hours. After holding, it is cooled to room temperature in the furnace to obtain the finished aluminum strip.
[0027] Testing revealed that the aluminum strip in this embodiment exhibited a conductivity of 68% IACS, a tensile strength of 112 MPa, and an elongation of 10%. High-resolution transmission electron microscopy (HRTEM) observation showed that a rare-earth-enriched passivation layer approximately 3 nm thick was formed at the interface between graphene and the aluminum substrate. This layer contained cerium carbides, lanthanum carbides, and aluminum rare-earth intermetallic compounds. The aluminum substrate exhibited distinct... <111> Rolled texture, graphene is oriented along the rolling direction.
[0028] Example 2 The high conductivity aluminum strip in this embodiment uses 1070 pure aluminum as the matrix. By mass percentage, the addition of graphene is 0.1%, cerium is 0.1%, and lanthanum is 0.2%. The mass ratio of cerium to lanthanum to graphene is 3:1, and the mass ratio of cerium to lanthanum is 1:2. The 1070 pure aluminum contains 0.09% iron, 0.07% silicon, and a total impurity content of 0.24%. The graphene used is few-layer graphene with a sheet diameter of 2 to 5 μm, 2 to 4 layers, a carbon purity of 99.6%, and an oxygen content of 0.25%. The graphene composite powder is coated with nano-aluminum powder on the surface of the few-layer graphene using vapor deposition. The average particle size of the aluminum powder is one-eighth the diameter of the graphene sheet, forming a core-shell structure. This coating improves the wettability of graphene and molten aluminum and reduces the tendency for agglomeration.
[0029] The preparation process is as follows: S1 Matrix Melting and Rare Earth Purification: Place 1070 aluminum ingots in a resistance melting furnace and heat to 725℃ until completely melted. Add aluminum-cerium master alloy and aluminum-lanthanum master alloy in appropriate proportions, wherein the cerium mass fraction of the aluminum-cerium master alloy is 10% and the lanthanum mass fraction of the aluminum-lanthanum master alloy is 10%. Mechanically stir for 5 minutes until the master alloys are completely dissolved, then argon gas is introduced for rotary jet refining for 10 minutes. After refining, let stand for 10 minutes and remove the slag from the surface of the melt.
[0030] S2 Low-Temperature Dispersed Graphene: The melt treated with S1 is cooled to 685℃, and the prepared graphene composite powder is added uniformly through a closed feeding device. Electromagnetic stirring is activated, and an ultrasonic field is applied to the melt at a frequency of 25kHz and a power density of 1.2W / cm³. 3 Dispersion treatment for 8 minutes yields the melt to be cast.
[0031] S3 casting billet: The molten material to be cast is continuously cast and rolled into a casting strip billet with a thickness of 8mm. During the casting and rolling process, the exit temperature is controlled between 630℃ and 650℃.
[0032] S4 Rolling and Annealing: The cast strip billet is heated to 470℃ and held for 30 minutes before hot rolling in two passes with a total reduction of 75%, resulting in a billet thickness of 2 mm. This is followed by cold rolling in five passes, with a single-pass reduction controlled between 16% and 20%, for a total reduction of 60%, resulting in a cold-rolled aluminum strip thickness of 0.8 mm. The cold-rolled aluminum strip is then placed in an annealing furnace and annealed at a low temperature of 290℃ under argon protection for 2 hours. After holding, it is cooled to room temperature in the furnace to obtain the finished aluminum strip.
[0033] Testing revealed that the aluminum strip in this embodiment exhibited a conductivity of 72% IACS, a tensile strength of 118 MPa, and an elongation of 9%. High-resolution transmission electron microscopy (HRTEM) observation showed that a rare-earth-enriched passivation layer with a thickness of approximately 2.5 nm was formed at the interface between graphene and the aluminum substrate. This layer contained cerium carbides, lanthanum carbides, and aluminum rare-earth intermetallic compounds. The aluminum substrate exhibited strong [unclear - possibly referring to a specific characteristic or characteristic]. <111> Rolled texture, graphene is oriented along the rolling direction.
[0034] Example 3 The high conductivity aluminum strip in this embodiment uses 1070 pure aluminum as the matrix. By mass percentage, the addition of graphene is 0.2%, cerium is 0.2%, and lanthanum is 0.2%. The mass ratio of cerium to lanthanum to graphene is 2:1, and the mass ratio of cerium to lanthanum is 1:1. The 1070 pure aluminum contains 0.08% iron, 0.05% silicon, and a total impurity content of 0.22%. The graphene used is few-layer graphene with a sheet diameter of 2 to 5 μm, 2 to 4 layers, a carbon purity of 99.6%, and an oxygen content of 0.25%. The graphene composite powder is coated with nano-aluminum powder on the surface of the few-layer graphene using vapor deposition. The average particle size of the aluminum powder is one-eighth the diameter of the graphene sheet, forming a core-shell structure. This coating improves the wettability of graphene and molten aluminum and reduces the tendency for agglomeration.
[0035] The preparation process is as follows: S1 Matrix Melting and Rare Earth Purification: 1070 aluminum ingots are placed in a resistance melting furnace and heated to 735℃ until completely melted. Aluminum-cerium master alloy and aluminum-lanthanum master alloy are added in appropriate proportions, with the aluminum-cerium master alloy containing 10% cerium by mass and the aluminum-lanthanum master alloy containing 10% lanthanum by mass. Mechanical stirring is performed for 6 minutes until the master alloys are completely dissolved. Then, argon gas is introduced for rotary jet refining for 7 minutes. After refining, the mixture is allowed to stand for 12 minutes, and the slag on the surface of the melt is removed.
[0036] S2 Low-Temperature Dispersed Graphene: The melt treated with S1 is cooled to 700℃, and the prepared graphene composite powder is added uniformly through a closed feeding device. Electromagnetic stirring is activated, and an ultrasonic field is applied to the melt at a frequency of 35kHz and a power density of 0.8W / cm³. 3 Dispersion treatment for 12 minutes yields the melt to be cast.
[0037] S3 casting billet: The molten material to be cast is poured into a flat billet with a thickness of 25mm, and the temperature is controlled at 690℃ during the casting process.
[0038] S4 Rolling and Annealing: The billet is heated to 490℃ and held for 30 minutes before hot rolling in 4 passes with a total reduction of 88%, resulting in a billet thickness of 3mm. This is followed by cold rolling in 7 passes, with a single-pass reduction controlled between 20% and 24%, resulting in a total reduction of 83.3%, and a cold-rolled aluminum strip thickness of 0.5mm. The cold-rolled aluminum strip is then placed in an annealing furnace and annealed at a low temperature of 310℃ under argon protection for 1 hour. After holding, it is cooled to room temperature in the furnace to obtain the finished aluminum strip.
[0039] Testing revealed that the aluminum strip in this embodiment exhibited a conductivity of 75% IACS, a tensile strength of 125 MPa, and an elongation of 8%. High-resolution transmission electron microscopy (HRTEM) observation showed that a rare-earth-enriched passivation layer with a thickness of approximately 4 nm was formed at the interface between the graphene and the aluminum substrate. This layer contained cerium carbides, lanthanum carbides, and aluminum rare-earth intermetallic compounds. <111> The rolling process produces the highest texture strength, and the graphene exhibits a significant directional alignment effect along the rolling direction.
[0040] Comparative Example 1 This comparative example uses the same 1070 pure aluminum as Example 1, without adding graphene, cerium, and lanthanum. It employs the same smelting, casting, hot rolling, cold rolling, and annealing processes as Example 1 to produce an aluminum strip with a thickness of 1 mm.
[0041] Testing revealed that the aluminum strip in this comparative example has a conductivity of 61.8% IACS, a tensile strength of 95 MPa, and an elongation of 12%. The aluminum matrix exhibits no obvious preferred texture.
[0042] Comparative Example 2 This comparative example uses the same 1070 pure aluminum as in Example 1, with only 0.05% graphene added, and no cerium or lanthanum added. The preparation process employs a one-step melting method, directly adding uncoated graphene powder at 730°C, stirring until homogeneous, then refining and casting. Subsequent rolling and annealing processes are identical to those in Example 1, producing an aluminum strip with a thickness of 1 mm.
[0043] Testing revealed that the aluminum strip in this comparative example had a conductivity of 63.5% IACS, a tensile strength of 102 MPa, and an elongation of 9%. Metallographic observation showed that the graphene exhibited significant agglomeration, and discontinuous aluminum carbide phases were present at the interface.
[0044] Comparative Example 3 This comparative example uses the same 1070 pure aluminum as in Example 1, with only 0.15% cerium and 0.15% lanthanum added, and no graphene added. The preparation process is the same as steps S1, S3, and S4 of Example 1, except that the graphene addition step in S2 is omitted, resulting in an aluminum strip with a thickness of 1 mm.
[0045] Testing revealed that the aluminum strip in this comparative example has a conductivity of 64.2% IACS, a tensile strength of 105 MPa, and an elongation of 11%. The aluminum matrix exhibits weak [variables / effects]. <111> Rolled texture.
[0046] Comparison table of key performance indicators between the examples and comparative examples: The data in the table shows that adding rare earth elements or graphene alone only slightly improves the conductivity of the aluminum strip. The combined conductivity improvement from adding either element alone is approximately 4.1% IACS, while the conductivity improvement in Example 1 reaches 6.2% IACS, significantly higher than the effect of simple addition, indicating that rare earth elements and graphene form an effective synergistic effect. Simultaneously, the aluminum strip of this invention has higher tensile strength than pure aluminum substrate and maintains a high elongation, balancing conductivity and processing performance. By adjusting the component ratios and process parameters, the conductivity can be adjusted within a wide range to adapt to the application requirements of different scenarios, with minimal performance fluctuations during mass production.
[0047] The high conductivity aluminum strip described in this invention can be directly stamped into various heat dissipation devices, such as heat sinks for electronic devices and heat dissipation substrates for power modules. Its high electrical and thermal conductivity accelerates heat transfer and reduces the operating temperature of the devices. Simultaneously, the lightweight nature of aluminum reduces the overall weight of the equipment. This aluminum strip can also be used to manufacture flexible connections for power batteries in new energy vehicles. It can be directly stamped or cut into connecting pieces, or it can be combined with copper strips to form copper-aluminum composite conductive strips. This reduces the cross-sectional area of the components while maintaining the same current carrying capacity, thus reducing heat loss at the connection points.
[0048] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A high conductivity aluminum strip, characterized in that, The aluminum strip uses 1070 pure aluminum as a base and contains graphene, cerium, and lanthanum. By mass percentage, graphene is 0.005%–0.5%, cerium is 0.02%–0.3%, and lanthanum is 0.02%–0.3%. The mass ratio of the total mass of cerium and lanthanum to the mass of graphene is 2:1–10:
1. The conductivity of the aluminum strip is not less than 62% IACS.
2. The high conductivity aluminum strip according to claim 1, characterized in that, The mass ratio of cerium to lanthanum is 1:1 to 1:
2.
3. The high conductivity aluminum strip according to claim 1, characterized in that, The graphene is few-layer graphene with a sheet diameter of 0.5–10 μm, 1–5 layers, a carbon purity of not less than 99.5%, and an oxygen content of not more than 0.3%.
4. The high conductivity aluminum strip according to claim 1, characterized in that, The impurities in the 1070 pure aluminum have an iron content of no more than 0.12%, a silicon content of no more than 0.08%, and a total impurity content of no more than 0.3%.
5. The high conductivity aluminum strip according to claim 1, characterized in that, A rare earth enriched passivation layer is formed at the interface between the graphene and the aluminum substrate. The thickness of the rare earth enriched passivation layer is 2-5 nm, and it contains cerium carbide, lanthanum carbide and aluminum rare earth intermetallic compounds.
6. The high conductivity aluminum strip according to claim 1, characterized in that, The aluminum matrix is formed <111> Rolled texture, graphene is oriented along the rolling direction.
7. A method for preparing a high conductivity aluminum strip, the method being used to prepare the high conductivity aluminum strip according to any one of claims 1 to 6, characterized in that, The preparation method includes the following steps: S1 matrix smelting and rare earth purification: 1070 aluminum ingots are heated to 720-740℃ and completely melted. Aluminum-cerium master alloy and aluminum-lanthanum master alloy are added, stirred evenly, and then refined with inert gas. After standing, the surface slag is removed. S2 Low-Temperature Dispersed Graphene: The melt treated by S1 is cooled to 680-710℃, and pre-coated graphene composite powder is added. Electromagnetic stirring combined with ultrasonic field-assisted dispersion is used to obtain the melt to be cast after dispersion. S3 casting billet: The molten material to be cast is made into a billet by casting or continuous casting and rolling; S4 Rolling and Annealing: The billet is hot-rolled and cold-rolled to the target thickness in sequence, and then annealed at low temperature to obtain the finished aluminum strip.
8. The method for preparing a high conductivity aluminum strip according to claim 7, characterized in that, In step S2, the graphene composite powder is a core-shell structured powder with a surface coated with nano-aluminum powder; the frequency of the ultrasonic field is 20–40 kHz, and the power density is 0.5–1.5 W / cm². 3 The dispersion time is 5 to 15 minutes.
9. The method for preparing a high conductivity aluminum strip according to claim 7, characterized in that, In step S4, the hot rolling opening temperature is 450-500℃, and the total hot rolling reduction rate is not less than 75%; the total cold rolling reduction rate is not less than 60%, and the single-pass reduction rate is 15%-25%; the low-temperature annealing temperature is 280-320℃, and the holding time is 1-2 hours.
10. The application of the high conductivity aluminum strip according to any one of claims 1 to 6 in heat dissipation devices, soft connections for new energy vehicle batteries, or copper-aluminum composite conductive strips.
